Effect of balance and proprioceptive training on balancing and technical skills in 13-14-year-old youth basketball players - Zacharakis, E. D.; Bourdas, D. I.; Kotsifa, M. I.; Bekris, E. M.; Velentza, E. T.; Kostopoulos, N. I. (Journal of Physical Education and Sport, 2020)
Introduction: Balance and proprioceptive training programs improve balance and positively a effect on technical skills in different sports. However, there is lack of research on the effect of balance training in basketball specifically for 13-14 year old youth athletes. The purpose of this study was to identify the effect of a balance and proprioceptive training program on dynamic and static balance and on technical skills in youth basketball players.